2010
DOI: 10.1016/j.nuclphysa.2010.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the nucleon structure function in the nuclear medium and evaluation of its moments

Abstract: We report on the measurement of inclusive electron scattering off a carbon target performed with CLAS at Jefferson Laboratory. A combination of three different beam energies 1.161, 2.261 and 4.461 GeV allowed us to reach an invariant mass of the final-state hadronic system W ≈ 2.4 GeV with four-momentum transfers Q 2 ranging from 0.2 to 5 (GeV/c) 2 . These data, together with previous measurements of the inclusive electron scattering off proton and deuteron, which cover a similar continuous two-dimensional reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…Such systematic information would be invaluable for estimating systematic uncertainties in neutrino-oscillation experiments. [84] and (b) carbon experiment E2 [85] deduced from the data reported for the F 2 structure functions.…”
Section: Appendix C: Other Existing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Such systematic information would be invaluable for estimating systematic uncertainties in neutrino-oscillation experiments. [84] and (b) carbon experiment E2 [85] deduced from the data reported for the F 2 structure functions.…”
Section: Appendix C: Other Existing Datamentioning
confidence: 99%
“…Liang et al [63,64] reported a detailed study of inclusive electron scattering in the resonance region, in which separated longitudinal and transverse response functions [81] and (b) carbon experiment E2 [82] deduced from the data reported for the F2 structure functions.…”
Section: Proton Literaturementioning
confidence: 99%
“…They have used the model to study the modification of F 2 structure functions in the nuclear medium and have suggested that the change the spin structure function of a bound nucleon in the nuclear matter is roughly twice as large as the change in the spin independent structure function. It may be mentioned that recently Osipenko et al [30] have reported the measurement of inclusive electron scattering from CLAS at JLab. They have evaluated the F 2 structure functions and the corresponding moments.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear if the extended scaling of the EMC ratio will hold true in the presence of significant contributions from quasielastic scattering [5,102,103]. Figure 13 shows the quasielastic contribution, σ qe /σ Born , based on our crosssection model for the 40 degree kinematics.…”
Section: K Scaling Violation Effects At High Xmentioning
confidence: 99%